Perencanaan Manajemen Sumber Daya Manusia dan Dampaknya Terhadap Kinerja Pegawai : Studi di PT PLN Indonesia Power Suralaya - Krisloana Kendali; Wawan Prahiawan (Journal of Management and Social Sciences, 2024)
Human resource planning is one of the most important assets in a company because it can improve employee performance. This research aims to analyze the influence of human resource management planning which consists of five targets, namely workforce planning, recruitment, selection, orientation and placement, as well as training and development on employee performance. The research method uses a quantitative approach with samples taken of 100 employees at PT PLN Indonesia Power Suralaya using proportional random sampling. Data collection was carried out through distributing online questionnaires which were then analyzed using SEM-PLS. The research results concluded that planning, selection, orientation and placement, training and development are functions of human resource management planning which are proven to contribute positively to improving performance. Meanwhile, recruitment has no effect on performance. The path coefficient value shows that selection is the most dominant variable influencing the good and bad of employee performance